Methylated Nucleobases: Synthesis and Evaluation for Base Pairing In Vitro and In Vivo. Issue 48 (23rd July 2018) - Jabgunde, Amit M.; Jaziri, Faten; Bande, Omprakash; Froeyen, Matheus; Abramov, Mikhail; Nguyen, Hoai; Schepers, Guy; Lescrinier, Eveline; Pinheiro, Vitor B.; Pezo, Valérie; Marlière, Philippe; Herdewijn, Piet
Abstract: The synthesis, base pairing properties and in vitro (polymerase) and in vivo ( E. coli ) recognition of 2′‐deoxynucleotides with a 2‐amino‐6‐methyl‐8‐oxo‐7, 8‐dihydro‐purine (X ), a 2‐methyl‐6‐thiopurine (Y ) and a 6‐methyl‐4‐pyrimidone (Z ) base moiety are described. As demonstrated by Tm measurements, theX andY bases fail to form a self‐complementary base pair. Despite this failure, enzymatic incorporation experiments show that selected DNA polymerases recognize theX nucleotide and incorporate this modified nucleotide versusX in the template. In vivo, X is mainly recognized as a A/G or C base;Y is recognized as a G or C base andZ is mostly recognized as T or C. Replacing functional groups in nucleobases normally involved in W−C recognition (6‐carbonyl and 2‐amino group of purine; 6‐carbonyl of pyrimidine) readily leads to orthogonality (absence of base pairing with natural bases). Abstract : Methylation of nucleobases at positions normally involved in W−C recognition of canonical bases readily leads to orthogonality.